Information Distorting Impact on Deliveries Planning Efficiency - Iouri SEMENOV; Ludmila FILINA-DAWIDOWICZ; Daria MOZDRZEN (Communications of International Proceedings, 2021)
When planning the delivery of cargo to the customers the logistics companies come together with a number of difficulties, especially related to the deformation/ distortion of information received and as result taking misguide actions by business-partners. This presents the challenge of making the right decisions dealing with choosing the appropriate supplier of products or services. In the article the thesis was put forward that the information provided when ordering goods can be subjected to distortion, which can cause wrong decisions taken by the company carrying out these orders. In particular, the folding of the contract may contain inaccurate information about the purchased products, the conditions of order execution, etc. The article analyses information distortions that occur at the stage of goods deliveries planning. A categorization of suppliers credibility has been proposed. The main causes of information distortions in the supply chains were compiled. It was found that the detection of information distortions sources, which while interacting create i.e. a synergy effect, is the most problematic.
Keywords: Supply chain; information distortion; decision making; supply planning; transportation.